Ulcerative Colitis Concomitant with Cytomegalovirus Infection, Bullous Sweet’s Syndrome, and Acute Myeloid Leukemia: A Case Report and Literature Review - Zhu F; Hu Z; Yu W; Dai F; Jing D; Zhou G (Dove Medical Press, 2023)
Fengqin Zhu,1,2 Zongjing Hu,1 Wei Yu,1 Fengxian Dai,1 Dehuai Jing,1 Guangxi Zhou1 1Department of Gastroenterology, Affiliated Hospital of Jining Medical University, Jining Medical University, Jining, Shandong, 272000, People's Republic of China; 2Shandong University of Traditional Chinese Medicine, Jinan, Shandong, 250355, People's Republic of ChinaCorrespondence: Guangxi Zhou, Department of Gastroenterology, Affiliated Hospital of Jining Medical University, Jining Medical University, Jining, Shandong, 272000, People's Republic of China, Email zgx_viola@126.comBackground: Ulcerative colitis (UC) is a chronic, relapsing progressive inflammatory immune disease. There is still no cure for it. Even worse, UC may predispose patients to opportunistic infections, and several extra-intestinal manifestations (EIMs) and comorbidities may antedate, occur with, or postdate the onset of UC, which may increase the mortality risk. But case reports of UC patients simultaneously concomitant with opportunistic infection, EIM, and comorbidity are extremely rare.Case Presentation: We report a case of 51-year-old male patient with incipient UC accompanied by cytomegalovirus (CMV) infection and bullous Sweet's syndrome (bSS, a cutaneous EIM of UC) after treatment with oral mesalazine and prednisolone for 3 weeks. After clearance of the CMV infection by using ganciclovir, the patient was administered two cycles of infliximab to cure UC and bSS; however, he developed acute myeloid leukemia (AML) a month later and died after two cycles of chemotherapy.Conclusion: Based on this rare case of UC concomitant with CMV infection, bSS and AML, we recommend that it is important to distinguish between an acute UC flare and opportunistic infections, especially in patients receiving immunosuppressive therapy, and monitor EIMs and comorbidities timely. Particular attention should be paid to cancer surveillance. Clinicians should be mindful of these facts to adopt optimal therapeutic options to address all aspects of UC. Early initiation of biological therapy may be of benefit to patients with newly diagnosed severe UC.Keywords: ulcerative colitis, cytomegalovirus, bullous Sweet's syndrome, acute myeloid leukemia